Cam impingement: defining the presence of a cam deformity by the alpha angle: data from the CHECK cohort and Chingford cohort - Agricola, R; Waarsing, J; Thomas, G; Glyn-Jones, S; al., E (Elsevier, 2014)
Cam impingement is characterized by abnormal contact between the proximal femur and acetabulum caused by a non-spherical femoral head, known as a cam deformity. A cam deformity is usually quantified by the alpha angle; greater alpha angles substantially increase the risk for osteoarthritis (OA). However, there is no consensus on which alpha angle threshold to use to define the presence of a cam deformity.To determine alpha angle thresholds that define the presence of a cam deformity and a pathological cam deformity based on development of OA.Data from both the prospective CHECK cohort of 1002 individuals (45-65 years) and the prospective population-based Chingford cohort of 1003 women (45-64 years) with respective follow-up times of 5 and 19 years were combined. The alpha angle was measured at baseline on anteroposterior radiographs, from which a threshold for the presence of a cam deformity was determined based on its distribution. Further, a pathological alpha angle threshold was determined based on the highest discriminative ability for development of end-stage OA at follow-up.A definite bimodal distribution of the alpha angle was found in both cohorts with a normal distribution up to 60°, indicating a clear distinction between normal and abnormal alpha angles. A pathological threshold of 78° resulted in the maximum area under the ROC curve.Epidemiological data of two large cohorts shows a bimodal distribution of the alpha angle. Alpha angle thresholds of 60° to define the presence of a cam deformity and 78° for a pathological cam deformity are proposed.